Genetic Associations With Gestational Duration and Spontaneous Preterm Birth. Issue 2 (June 2018) - Zhang, G.; Feenstra, B.; Bacelis, J.; Liu, X.; Muglia, L.M.; Juodakis, J.; Miller, D.E.; Litterman, N.; Jiang, P.P.; Russell, L.; Hinds, D.A.; Hu, Y.; et al.
Abstract : ( N Engl J Med. 2017;377(12):1156–1167) Preterm birth is the leading cause of death in neonates and children above 5 years of age. Its definition, birth before 37 completed weeks of gestation, is a dichotomous trait based on a somewhat arbitrary cutoff of weeks' gestation, rather than time of birth or a level of fetal maturity. Therefore, in the present study, the authors tested genetic associations with gestational duration (a quantitative trait) and preterm birth (a dichotomous trait), in order to identify robust associations with genetic variants consistent with a role in the timing of birth.